Leadership pain : the classroom for growth - Chand, Samuel R. (Nashville, TN : Thomas Nelson, 2015)
"Do you want to be a better leader? Raise the threshold ofyour pain. Doyou want your church to grow or your business to reach higher goals? Reluctance to face pain is your greatest limitation. There is no growth without change, no change without loss, and no loss without pain. Bottom line : if you're not hurting, you're not leading"-- Back cover.
Leadership Leprosy -- External challenges -- Too much too often -- Growing pains -- What makes you tick -- Root cause analysis -- You gotta love it -- Privilege of leadership -- Power of tenacity -- pain partners -- It's your move.
"Next leadership network."
Includes bibliographical references.
Keywords: Leadership -- Religious aspects; Christian leadership